The effect of filler content and chemical modification on properties of polylactic acid/recycled low density polyethylene/nypa fruticans husk biocomposites - Mohamad Syahmie Mohamad Rasidi (School of Materials Engineering, 2015)
This scope of study focused on tensile properties, morphology, thermal properties, enzymatic degradation and FTIR. Tensile testing to measure tensile strength, elongation at break and tensile modulus of biocomposites. The differential scanning calorimetric (DSC) and thermogravimetric analysis (TGA) used to investigate the thermal properties of biocomposites. The morphology study of the tensile fracture surface of biocomposites carried out by using scanning electron microscope (SEM). The enzymatic biodegradation to study the biodegradation rate of biocomposites subjected to enzyme. The functional group of untreated and treated NFH were determined using FTIR.